Hysteresis in cloud heights during solid suspension in stirred tank reactor: experiments and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Aiche Journal, 2010)
Solid suspension in stirred tank reactor is widely used in process industries for catalytic reactions, dissolution of solids, crystallization, and so on. Suspension quality is a key issue in design and operation of stirred reactor and its determination is not straight forward. Cloud height measurements of solid suspension provide a relatively simple way to quantify quality of suspension. In this work, experiments were carried out to quantify variation of cloud heights with impeller speed and particle characteristics. These measurements were carried out using visual observations, image analysis, and ultrasound velocity profiler techniques. The obtained data demonstrated the existence of hysteresis in cloud heights with respect to impeller speed. Apart from possible applications in reducing power required for achieving desired solid suspension quality, the existence of hysteresis also provides a new way to evaluate computational fluid dynamics (CFD) simulations of solid liquid flows in stirred vessels. An attempt was made to capture observed hysteresis in cloud heights in CFD simulations. The simulated results were compared with the experimental data. The presented models and results (experimental and computational) will he useful for simulating complex solid liquid flows in stirred reactors. (C) 2010 American Institute of Chemical Engineers AIChE J, 56: 2795-2804, 2010
Keywords: CFD; hysteresis in cloud height; solid velocity profiles

Solid suspension in stirred tanks: UVP measurements and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
Suspension of solids in stirred reactor is widely used for catalytic reactions, dissolution, etc. Quality of solid suspension is an important parameter required for the reliable design, optimum performance, and scale up of the system. Quality of suspension depends on local characteristics of solid velocity and hold up profiles. The present work was focused on investigating quality of solid suspension using ultrasound velocity profiler (UVP) measurements and CFD simulations. The slip velocity measurements carried out with UVP were used to evaluate different drag correlations used in CFD simulations. Results discussed in this work would be useful for extending the applications of CFD models for simulating large stirred slurry reactors.
Keywords: CFD; drag coefficient; solid suspension; solid-liquid velocities; UVP

Two-phase flow boiling in 19mm tube: experiments and CFD modelling - Sardeshpande, Madhavi V.; Raymond, Barlev; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2016)
Boiling flows are encountered in a wide range of industrial applications such as boilers, nuclear reactors, electronic cooling, and various types of chemical reactors. Heat transfer coefficients, flow boiling regimes, flow instabilities, pressure drops, and conditions like dry-out are some of the key issues in every boiling flow study. It is observed that a limited experimental database is available for the 19mm ID channel diameter, i.e. a typical tube diameter of steam generator. Therefore, in the present work, the experimental setup was designed for studying boiling flows in a 19mm ID tube in such a way that different flow regimes occurring in a steam generator tube (from pre-heating of sub-cooled water to dry-out) could be investigated by varying inlet conditions. The reported results cover a reasonable range: 8-27kW/m(2) and 2.9-5.9kg/m(2)s heat and mass flux conditions, respectively. A basic computational flow model was also developed to facilitate interpretation of the obtained data. The presented design of the experimental setup and the approach of mimicking different types of steam generator tubes as well as presented experimental and simulated results are useful for gaining insight into complex boiling flows in tubes, and provide a sound basis for further work in this area.
Keywords: CFD; Flow regimes; two-phase flow boiling; vapour quality